Obstetrics - Procházka, Martin; Pilka, Radovan (Palacký University Olomouc, 2012)
Obstetrics is an integral part of medical education. Doctors from different specialties meet pregnant women more frequenty as the care has become more complex nowadays. The target group of this textbook are not only medical students but also primary care doctors providing basic and up to date facts on obstetrics. We hope this book will be beneficial for all readers.
Textbooks
Keywords: gynekologie a porodnictví; Obstetrics; porodnictví